Remedy for now but prohibit for tomorrow: the deterrence effects of merger policy tools - Jo Seldeslachts; Joseph A. Clougherty; Pedro Pita Barros (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Antitrust policy involves not just the regulation of anti-competitive behavior, but also an important deterrence effect. Neither scholars nor policymakers have fully researched the deterrence effects of merger policy tools, as they have been unable to empirically measure these effects. We consider the ability of different antitrust actions – Prohibitions, Remedies, and Monitorings – to deter firms from engaging in mergers. We employ cross-jurisdiction/pan-time data on merger policy to empirically estimate the impact of antitrust actions on future merger frequencies. We find merger prohibitions to lead to decreased merger notifications in subsequent periods, and remedies to weakly increase future merger notifications: in other words, prohibitions involve a deterrence effect but remedies do not. – – Wettbewerbspolitik ist nicht nur Regulierung von wettbewerbsfeindlichem Verhalten, sondern hat auch eine wesentliche Abschreckungswirkung. Weder Wissenschaftler noch politische Entscheidungsträger haben die Abschreckungswirkung von Wettbewerbspolitik vollständig untersucht, da es sehr schwierig ist diese Wirkung empirisch nachzuweisen. Wir untersuchen die Wirkung verschiedener wettbewerbspolitischer Maßnahmen – Untersagung, Auflagen und Monitoring – um Unternehmen von Zusammenschlüssen abzuhalten. Wir nutzen einen Panel-Datensatz, um den Einfluss von Wettbewerbspolitik auf die künftige Anzahl von Firmenzusammenschlüssen zu bewerten. Wir zeigen, dass die Untersagung von Zusammenschlüssen die Fusionsankündigung in der Zukunft reduziert, und dass Fusionsauflagen künftige Ankündigungen schwach ansteigen lassen. Anders gesagt: Untersagungen haben eine führen zu Abschreckungswirkung, Auflagen nicht.
Keywords: L40; L49; K21; 330; merger policy tools; deterrence effects; cross-section/time-series data